Teachers' perspective of English learning models amidst pandemic: Online and offline learning - Farida Hamid; Dhila Nurul Azmi; Muhammad Sabaniyah; Nida Husna; Dinnisa Haura Zhafira Hidayat (Universitas Cokroaminoto Palopo, 2022)
The purpose of this study is to find out the teacher's perspective on online learning and offline learning. With the advancement of technology, a new trend in the classroom has developed primarily during the Pandemic. This qualitative descriptive study investigates teachers’ perspectives regarding online and offline learning; Two ninth-grade English teachers from SMPN 3 Cisauk, Banten, were involved in this study. The researchers used direct observation and interviews with two English teachers to obtain the data. The result showed that English teachers are more comfortable teaching students offline than online. Besides that, English teachers feel the maximum capacity to deliver the material chosen directly in the classroom. Meanwhile, in carrying out online learning, which is different from face-to-face learning, teachers must implement appropriate methods and media according to student needs. Finally, four recommendations are provided. Those are related to teachers’ efforts to improve the quality and suitability of the learning materials, institutional support (e.g., internet stipend), teachers’ readiness for Information and Technology, and attention to students’ difficulties in learning.